Factors Influencing Identification as a Fan and Consumerism towards The Virtual K-Pop Group MAVE: - Hoesan, Valencia; Nuraeni, Shimaditya (Journal of Consumer Studies and Applied Marketing, 2023)
The K-Pop industry has been developing Virtual K-Pop Group, a K-Pop group with virtual human members who are made to be as similar as possible to actual humans. Identification as a fan is one of the important factors in creating a purchasing behavior in the form of consumerism towards certain K-Pop groups. Therefore, this research was conducted with the aim of identifying factors that significantly influence identification as a fan and consumerism towards one of the well-known Virtual K-Pop Groups, which is MAVE:. This research uses an extended Theory of Planned Behavior framework with additional audio and visual components, virtual group concept, peer influence and social media influence as the variables. The method used in this research is quantitative and using a questionnaire with respondents from Indonesia who have at least once performed consumerism towards MAVE: as the data source. The data was analyzed using the Path Analysis method to examine the influence between variables, namely attitude, subjective norms, perceived behavioral control, identification as a MAVE: fan and consumerism towards MAVE:. The result indicates that virtual group concept’s influence towards attitude and peer influence’s influence towards subjective norms are positively significant. Attitude, subjective norms and perceived behavioral control positively significant in influencing identification as a MAVE: fan. Also, identification as a MAVE: fan significantly influences consumerism towards MAVE: positively. The findings of this research is aimed to understand the consumer behavior of Virtual K-Pop Group consumers, so that it becomes the basis for label companies that produce these groups to create effective strategies for generating revenue as the main goal of business.